Studi Pengetahuan Siswa terhadap Jenis, Khasiat dan Cara Pemanfaatan Tanaman Obat yang Terdapat di Lingkungan Sekolah - Diana Zulyetti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the extent of the knowledge of students of SMP Negeri 3 Payakumbuh District on the types, efficacy and ways of utilizing medicinal plants found in the school environment. The method in this study is a survey method. Sampling was done by taking 15% of all students in class VII and class VIII and obtained as many as 41 students. Data collection on students' knowledge of the types, benefits and methods of processing medicinal plants was carried out using a questionnaire. The results showed that 68.0% of SMP Negeri 3 Payakumbuh students knew the types of medicinal plants in the school environment with knowledge categorized as knowing, as many as 66.0% of students knew about the benefits of medicinal plants categorized as knowing, and 69, 9% of students know that processing medicinal plants is categorized as knowing. Conclusion, most students have knowledge about medicinal plants in the school environment with a category level to know, starting from the types, benefits and ways of managing medicinal plants. Keywords: knowledge, types, Benefits benefits, medicinal plants